Effects of task-based activities on young learner´s conversational strategies - Oliveira, Ana Débora Botica de (2020)
The present study focuses on oral peer interaction in primary English classrooms, aiming to explore which conversational strategies are employed by its participants to complete a series of three tasks while working in pairs, and how these strategies affect their ability to communicate. The conversational strategies investigated were divided into three categories, use of L1 for task-management purposes, negotiation of meaning strategies (clarification requests, confirmation checks, comprehension checks, self and other-repetition and prompts) and error correction strategies (self and other-correction). The participants were audio-recorded while completing the tasks, over a period of nine weeks. These recordings were subsequently transcribed, and the strategies identified coded according to the above-mentioned classification. This was followed by quantitative analysis, using grids to register the strategies produced by each pair in each task, to check for patterns of either consistency or variation regarding the frequency of the strategies used during the tasks. Finally, these findings were used to select relevant excerpts of the students’ spoken production and to examine them from a qualitative perspective to determine if and how the strategies used helped foster successful communication. Action research was the methodology adopted. Data collection tools consisted of the recordings made during the tasks, the teacher’s notes concerning events that took place during the setup, completion and feedback stages of the tasks, and data from the students’ self-assessment charts. The teacher’s notes included her perceptions and possible interpretation of these events, to complement the data from the recordings and to triangulate information. The students’ self-assessment charts registered the children’s own views on their progress regarding their interactional skills, as well as on their motivation and level of engagement with the task. Results showed that conversational strategies seem to play an important role in peer interaction, as they were used in nearly half of the children’s production. Firstly, despite significant variation between tasks and pairs, L1 for task management purposes was the most frequently used strategy, with students resorting to L1 to address procedural-related issues and to codeswitch when their knowledge of English was insufficient to convey the message. However, there seemed to be a broad tendency for using less L1 over time. Secondly, frequency of negotiation of meaning strategies was relatively low, with weaker students mostly resorting to strategies to ask for assistance, and stronger students mostly producing strategies to provide it, which pointed to the relevance of pair composition regarding the students’ level of proficiency. Thirdly, a very low number of error-correction strategies were identified. However, the fact that children showed some improvement regarding their oral interaction skills suggests they do benefit from this type of activity, not by producing modified output, which was very rarely found, but by paying attention to form, working with formulaic language and developing additional social and cognitive skills as well as their motivation and confidence as speakers of English.